KONSTRUKSI DAN TRANSMISI MEMORI KOLEKTIF TENTANG KAHAR MUZAKAR DALAM KONFLIK DI TORAJA - Sanya Randan; Windy Bara Tau; Wanda Kristiani; Risna Risna; Novita Teken; Yestika Ruku; Sintia Sintia (CENDEKIA: Jurnal Ilmu Pengetahuan, 2026)
This study aims to understand how the Toraja community constructs collective memory regarding the Kahar Muzakkar rebellion and to examine how the experience of the conflict influenced the social life of the people in Tana Toraja and North Toraja. This research uses a qualitative approach with a descriptive research type. Data were obtained through in-depth interviews with seven informants who had experiences and memories related to the Kahar Muzakkar rebellion and were supported by relevant literature. The results show that the collective memory of the community regarding the Kahar Muzakkar movement was formed through direct experiences and oral narratives passed down across generations within families and communities. The presence of armed groups created fear, psychological pressure, disruption of economic and social activities, and collective trauma that continues to live in the memory of the community. In dealing with the conflict situation, the Toraja people tended to take a neutral position as a survival strategy, while religious and traditional leaders played important roles in maintaining social stability and preserving local values. The memory of the conflict has continued to be transmitted and has become part of how the community understands local history and social relations within their environment. This study concludes that the Kahar Muzakkar rebellion not only left traces of political and military conflict, but also shaped the social memory structure of the Toraja community in a sustainable manner. ABSTRAK Penelitian ini bertujuan untuk memahami bagaimana masyarakat Toraja membangun memori kolektif terhadap peristiwa Pemberontakan Kahar Muzakkar serta melihat pengaruh pengalaman konflik tersebut dalam kehidupan sosial masyarakat di Tana Toraja dan Toraja Utara. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian deskriptif. Data diperoleh melalui wawancara mendalam terhadap tujuh informan yang memiliki pengalaman dan ingatan mengenai peristiwa Kahar Muzakkar serta didukung oleh literatur yang relevan. Hasil penelitian menunjukkan bahwa memori kolektif masyarakat mengenai gerakan Kahar Muzakkar terbentuk melalui pengalaman langsung dan cerita lisan yang diwariskan secara antargenerasi dalam lingkungan keluarga maupun masyarakat. Kehadiran pasukan bersenjata menimbulkan rasa takut, tekanan psikologis, terganggunya aktivitas ekonomi dan sosial, serta membentuk trauma kolektif yang masih terus hidup dalam ingatan masyarakat. Dalam menghadapi situasi konflik, masyarakat Toraja cenderung mengambil posisi netral sebagai strategi bertahan hidup, sementara tokoh agama dan tokoh adat berperan penting dalam menjaga stabilitas sosial dan mempertahankan nilai-nilai lokal masyarakat. Ingatan mengenai konflik tersebut kemudian terus diwariskan dan menjadi bagian dari cara masyarakat memandang sejarah lokal dan relasi sosial di lingkungan mereka. Penelitian ini menyimpulkan bahwa peristiwa Kahar Muzakkar tidak hanya meninggalkan jejak konflik politik dan militer, tetapi juga membentuk struktur memori sosial masyarakat Toraja secara berkelanjutan.